2022
DOI: 10.1002/jmv.27757
|View full text |Cite
|
Sign up to set email alerts
|

Variant‐specific SARS‐CoV‐2 within‐host kinetics

Abstract: Since early 2021, SARS‐CoV‐2 variants of concern (VOCs) have been causing epidemic rebounds in many countries. Their properties are well characterized at the epidemiological level but the potential underlying within‐host determinants remain poorly understood. We analyze a longitudinal cohort of 6944 individuals with 14 304 cycle threshold ( Ct ) values of reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR) VOC screening tests performed in the general population and hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…The increased transmissibility of Alpha over previously circulating lineages may be explained by higher viral loads; mean N- and E-gene Ct value was approximately 1 lower for Alpha relative to wild-type lineages. This result matches other work that suggested the Alpha variant has higher viral loads than previously circulating lineages [46]. However, it is possible that both analyses have been influenced by the high growth rate of Alpha during its emergence relative to other lineages, which could lead to a difference in the observed distribution generated by differences in the average time since infection [47].…”
Section: Discussionsupporting
confidence: 87%
“…The increased transmissibility of Alpha over previously circulating lineages may be explained by higher viral loads; mean N- and E-gene Ct value was approximately 1 lower for Alpha relative to wild-type lineages. This result matches other work that suggested the Alpha variant has higher viral loads than previously circulating lineages [46]. However, it is possible that both analyses have been influenced by the high growth rate of Alpha during its emergence relative to other lineages, which could lead to a difference in the observed distribution generated by differences in the average time since infection [47].…”
Section: Discussionsupporting
confidence: 87%
“…[2][3][4] Early detection also enables earlier initiation and more effective treatments. [5][6][7][8] Testing strategies to achieve detection in the pre-infectious and infectious periods of new SARS-CoV-2 variants or new viruses requires filling two critical knowledge gaps: (1) Which respiratory specimen accumulates virus first? (2) What is the appropriate test analytical sensitivity to detect the earliest accumulation of virus (in the pre-infectious and infectious stages)?…”
Section: Introductionmentioning
confidence: 99%
“…As new SARS-CoV-2 variants-of-concern (and new respiratory viruses) emerge with different viral kinetics, 1 it is important to continually re-evaluate testing strategies (including specimen type and test analytical sensitivity) for detecting pre-infectious and infectious individuals. Early detection limits transmission within communities and the global spread of new variants.…”
Section: Introductionmentioning
confidence: 99%
“…138 The model with the lowest Akaike information criterion (with a ΔAIC <2) was chosen among other models in the study, where the selected model revealed a conspicuous difference in viral load between the nCoV lineage and the alpha variant with Cq values from qPCR, which were connected with the viral copies/ml values obtained from ddPCR. 138 The study also portrayed a slower decay rate of the alpha variant infections than in previous lineages. Such studies invariably show the potential use of…”
Section: Viral Concentration Monitoring In the Environmentmentioning
confidence: 99%